Calorie Restriction Attenuates Monocrotaline-induced Pulmonary Arterial Hypertension in Rats. Issue 6 (June 2015) - Ding, Mingge; Lei, Jingyi; Qu, Yinxian; Zhang, Huan; Xin, Weichuan; Ma, Feng; Liu, Shuwen; Li, Zhichao; Jin, Faguang; Fu, Enqing
Abstract : Abstract: Calorie restriction (CR) is one of the most effective nonpharmacological interventions protecting against cardiovascular disease, such as hypertension in the systemic circulation. However, whether CR could attenuate pulmonary arterial hypertension (PAH) is largely unknown. The PAH model was developed by subjecting the rats to a single subcutaneous injection of monocrotaline. CR lowered mean pulmonary arterial pressure (mPAP) and reduced vascular remodeling and right ventricular hypertrophy in PAH rats. Meanwhile, CR attenuated endothelial dysfunction as evidenced by increased relaxation in response to acetylcholine. The beneficial effects of CR were associated with restored sirtuin-1 (SIRT1) expression and endothelial nitric oxide synthase (eNOS) phosphorylation and reduced eNOS acetylation in pulmonary arteries of PAH rats. To further clarify the role of SIRT1 in the protective effects of CR, adenoviral vectors for overexpression of SIRT1 were administered intratracheally at 1 day before monocrotaline injection. Overexpression of SIRT1 exhibited similar beneficial effects on mPAP and endothelial function, and increased eNOS phosphorylation and reduced eNOS acetylation in the absence of CR. Moreover, SIRT1 overexpression attenuated the increase in mPAP in hypoxia-induced PAH animals. Overall, the present data demonstrate that CR may serve as an effective treatment of PAH, and targeting the SIRT1/eNOS pathway may improve treatment of PAH.